2008
DOI: 10.1159/000138127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Balanced Mixture of Dietary Fibers on Gastric Emptying, Intestinal Transit and Body Weight

Abstract: Background/Aims: Dietary fibers are frequently included in diets to decrease body weight, but their scarce palatability and the occurrence of meteorism prevent a long-term intake. The aim of this study was to test a mixture of dietary fibers expressly chosen to decrease their negative properties and strengthen their positive effects. Methods: In a series of 10 patients with a slight overweight, the effectiveness of a palatable dietary fibers mixture on gastric emptying and intestinal transit was tested with sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Several studies conclude that organic foods differ from conventional foods in the quantity of antioxidants, fibre and dry matter 8, 19. Fibres stimulate healthy bowel function, give a feeling of satiety after meals and may play a role in weight loss 20, 21. In addition, for the perceived positive changes in the condition of skin, hair and nails, an explanation may be sought in the differences in nutrient composition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conclude that organic foods differ from conventional foods in the quantity of antioxidants, fibre and dry matter 8, 19. Fibres stimulate healthy bowel function, give a feeling of satiety after meals and may play a role in weight loss 20, 21. In addition, for the perceived positive changes in the condition of skin, hair and nails, an explanation may be sought in the differences in nutrient composition.…”
Section: Discussionmentioning
confidence: 99%
“…M. oleifera leaf powder also contain about 12% (w/w) fibers (Joshi and Mehta, 2010). Dietary fibers reduce gastric emptying (Bortolotti et al, 2008). They may partly explain the greater stomach content, the improved OGTT response in treated GK diabetic rats (Ndong et al, 2007b), as well as the progressive improvement of PPPG levels in treated T2DM patients (Ghiridhari et al, 2011).…”
Section: Pharmacology Of M Oleifera Leavesmentioning
confidence: 99%
“…Growing evidence showed that the physicochemical properties of dietary fiber such as viscosity, water-binding capacity, and fermentability may contribute to decrease the food intake in human beings and rodents [3,4,5]. Viscous fibers increase chewing activity and saliva production in the mouth [6], which could result in early satiation and reduced food intake [7,8].…”
Section: Introductionmentioning
confidence: 99%